1964
DOI: 10.1021/ja01062a034
|View full text |Cite
|
Sign up to set email alerts
|

The Biosynthesis of Nicotine in Nicotiana glutinosa from Carbon-14 Dioxide

Abstract: the N-methylgroup, and carpon~2' of the pyrrolid'~ri.-~.•:~ihg_wa~.• determined. These data were correlated in terms :Of~•Ji)> the . .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1964
1964
1981
1981

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The high rate of incorporation of radioactivity into the total alkaloids as well as into thebaine and reticuline both in seedlings and in mature F 1 varlipr work in this laboratory (Rapoport et al, 1960; Stermitz and Rapoport, 1961) established the rapid de novo synthesis of thebaine (I) (Chart I) from 14C02 and its primacy in the hydrophenanthrene alkaloid series. These reports together with similar studies on the biosynthesis of nicotine alkaloids (Alworth et al, 1964;Liebman et al, 1965Liebman et al, , 1967 provide adequate demonstration of the value of the method which involves growing plants in the presence of 14C02 and determining the relative rates and amounts of radioactivity incorporated into different molecules or different portions of the same molecule. Barton and Cohen (1957) earlier suggested the diphenolic alkaloid, reticuline (Ha), as a likely precursor of thebaine (I).…”
mentioning
confidence: 83%
“…The high rate of incorporation of radioactivity into the total alkaloids as well as into thebaine and reticuline both in seedlings and in mature F 1 varlipr work in this laboratory (Rapoport et al, 1960; Stermitz and Rapoport, 1961) established the rapid de novo synthesis of thebaine (I) (Chart I) from 14C02 and its primacy in the hydrophenanthrene alkaloid series. These reports together with similar studies on the biosynthesis of nicotine alkaloids (Alworth et al, 1964;Liebman et al, 1965Liebman et al, , 1967 provide adequate demonstration of the value of the method which involves growing plants in the presence of 14C02 and determining the relative rates and amounts of radioactivity incorporated into different molecules or different portions of the same molecule. Barton and Cohen (1957) earlier suggested the diphenolic alkaloid, reticuline (Ha), as a likely precursor of thebaine (I).…”
mentioning
confidence: 83%
“…VII of "Techniques of Organic Chemistry," A. Weissberger, Ed., Interscience Publishers, Inc., New York, N. Y., 1955. We may extend our discussion to the competition between hydrogen abstraction and /3-scission by constructing an isokinetic temperature plot from the data of Table II as shown in Fig. 4. Here the results are rather more complicated.…”
Section: (I) Good Agreement Is Observed Withmentioning
confidence: 98%
“…The treatment of the solid support with alkali as a method of suppressing acid sites proved very fruitful in separating alkaloids. 16 " 21 The investigation of the Chromatographie behavior of HC (pyridine, furan, thiophene derivatives) on columns packed with the alkali-treated solid support revealed that alkali markedly reduced the solid support specific area, decreased discernibly retention times and effectively eliminated tailing effects in the case of pyridine bases; moreover, alkali participated in the separation process bringing about specific interactions. [22][23][24][25][26][27] In studying the separation of amines and nitrogen-containing HC (pyridine, piperidine, pyrrolidine, pyrrole, picolines), Golovnya et al likewise faced a problem of the specific influence of alkali on the liquid phase properties (polarity increase).…”
Section: Role Of the Solid Support In Gas-liquid Chromatography Omentioning
confidence: 99%
“…In particular pyrolysis of some indole alkaloids was performed at 350, 375, and 425°C and the chromatography of the pyrolysis products followed. 16,34 (1964).…”
Section: Gas-liquid Chromatography [6vidmentioning
confidence: 99%
See 1 more Smart Citation